MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS IV SDN 190 KOTANOPAN DENGAN PENERAPAN MODEL PEMBELAJARAN TUTOR SEBAYA - Nuriah Nuriah (Jurnal Guru Kita PGSD, 2017)
Abstract: Improving Student's Speaking Ability IV SDN 190 Kotanopan With The Application Of Peer Tutor Learning Model. This study aims to determine whether the activity learning class IV SDN 190 Kotanopan Year Learning 2016/2017 increased after applying the model Tutor Sebaya. This research was conducted at SDN 190 Kotanopan, Kotanopan Sub-district, Mandailing Natal Regency. Sample in this research as much as I (one) class that is class IV as many as 23 people. Student learning outcomes by applying model Tutor Sebaya in Formative I and Formative II show the average value of 64.78 and 83.91 as well as the individual completeness 13 students and 21 students and the completeness of the class is 56.52% and 91.30% of the data show the complete individual in accordance with KKM Language Indonesia is 65, with 91.30% classical completeness.Keywords: Learning Outcomes, Learning Activities, Peer Tutor.Abstrak: Meningkatkan Kemampuan Berbicara Siswa Kelas IV SDN 190 Kotanopan Dengan Penerapan Model Pembelajaran Tutor Sebaya. Penelitian ini bertujuan untuk mengetahui apakah aktivitas belajar kelas IV SDN 190 Kotanopan Tahun Pembelajaran 2016/2017 mengalami peningkatan setelah menerapkan model pembelajaran Tutor Sebaya. Penelitian ini dilakukan di SDN 190 Kotanopan, Kecamatan Kotanopan, Kabupaten Mandailing Natal. Sampel dalam penelitian ini sebanyak I (satu) kelas yaitu kelas IV sebanyak 23 orang. Hasil belajar siswa dengan menerapkan model pembelajaran Tutor Sebaya pada Formatif I dan Formatif II menunjukkan nilai rata-rata 64.78 dan 83.91 serta ketuntasan individu 13 siswa dan 21 siswa dan ketuntasan kelas adalah 56.52% dan 91.30% dari data tersebut menunjukkan tuntas individu sesuai dengan KKM Bahasa Indonesia yaitu 65, dengan ketuntasan klasikal 91.30%.Kata kunci : Hasil Belajar, Aktivitas belajar, Tutor Sebaya.